Utilization of Sentinel-2 satellite imagery for correlation analysis of shoreline variation and incident waves: Application to Wonpyeong-Chogok Beach, Korea - Euihyun Kim; Changbin Lim; Jung Lyul Lee (International Journal of Applied Earth Observations and Geoinformation)
Satellite images have been adopted in recent years for identifying topographical features on the Earth’s surface. Researchers have also published reports on the use of satellite images to analyze shoreline changes or to verify shoreline change in numerical models. But reports that demonstrate the reverse process of using satellite images to estimate the incident waves to a beach are rare, particularly to a place where protective coastal structures exist. This paper describes a once-thriving coastal townsite with two fishing ports in Korea which has been transformed into a typical example that relies on protective structures with occasional artificial nourishment to maintain its shoreline stability in the past 20 years. Unlike many others, this study proposes a new methodology to estimate the deepwater wave heights based on the analysis of shoreline data extracted from satellite images over 5 years (2019–2023) for Wonpyeong-Chogok Beach, its median sediment grain sizes D50, and the known empirical relationship between sediment and waves. The entire shoreline of 2,860 m in length is divided into 39 transects, of which one-half of it is protected by submerged and emergent detached breakwaters, where shoreline has advanced, while the rest has eroded. From the standard deviation values ​​calculated from the extracted shoreline location data, the influence of long-term trends was excluded, and the intrinsic standard deviation is obtained by applying sediment size information, and then the incident deep-water (average annual maximum) wave height of 4.363 m was estimated. Applying this methodology to the beach area where the coastal structure was placed, the wave transmission of the coastal structure was calculated 0.91 and 0.72 for LCSs and TT-DBWs, respectively, through the reduction ratio of the standard deviation. Finally, discussions are made on how the resolution of the Sentinel-2 satellite images in affecting the standard deviation and long-term trend results in the shoreline data.